B1 mapping of short T2* spins using a 3D radial gradient echo sequence. Issue 5 (10th June 2013) - Kobayashi, Naoharu; Garwood, Michael
<x xml:space="preserve">Abstract</x> Purpose To develop a method to acquire a radiofrequency (B1) field map when the signal has a short T2*. Theory and Methods The method is based on the actual flip angle imaging (AFI) technique and a radial 3D gradient‐echo sequence known as COncurrent Dephasing and Excitation (CODE), which preserves short T2* signals. CODE was implemented with Gradient‐modulated Offset‐Independent Adiabaticity (GOIA) pulses to obtain high estimation sensitivity with AFI. The correlation method, which removes the quadratic phase from the frequency‐modulated pulse excitation, was modified to handle gradient‐modulated pulses. Validity of the modified correlation procedure was tested by Bloch simulations. CODE experiments with sinc, hyperbolic secant, and GOIA pulses were performed in order to see effects from the frequency and gradient modulation. Finally, GOIA‐CODE AFI was conducted and compared with conventional AFI with 3D gradient echo (GRE). Results The modified correlation method developed to accommodate frequency and gradient modulations of GOIA performed well as judged by the minimal impact on reconstructed image quality. GOIA‐CODE AFI provided flip angle maps consistent with those measured by GRE AFI when the T2* was long (>2 ms) and continued to perform well for short T2* signals. Conclusion The proposed technique provides a means to obtain a 3D B1 field map when imaging spins with short T2*. Magn Reson Med 71:1689–1699, 2014. © 2013 Wiley Periodicals, Inc.